Practical non-destructive testing - Raj, Baldev , 1947-; Jayakumar, T.; Thavasimuthu, M. (Alpha Science International, 2007)
Aims to cover the principles, procedures, applications, limitations, codes and standards widely used in non-destructive testing (NDT) techniques. In this book, the authors added techniques on Neutron radiography, Pulsed Eddy Current Testing, Low Frequency Eddy Current Testing, SQUID based Eddy Current Testing and Mechanical Impedance Analysis